Kelayakan Usaha Budi Daya Rumput Laut Kappaphycus Alvarezii dengan Metode Longline dan Strategi Pengembangannya di Perairan Karimunjawa - Heryati Setyaningsih; Komar Sumantadinata; Nurheni Sri Palupi (Institut Pertanian Bogor, 2012)
The most widely cultivated seaweed in aquatic Karimunjawa is Kappaphycus alvarezii, because low venture capital, high market demand, low-cost production technology, production cycle is short, post-harvest handling is easy, and simple as well as market share is still open. This study aims to (1) Evaluate the feasibility of seaweed cultivation; (2) Identify factors that influence internal and external business seaweed cultivation; (3) Develop appropriate strategies in business development efforts to the cultivation of seaweed. Financial data were analyzed according to the criteria value NPV, B/C ratio, IRR, PBP, and BEP. Identification of environmental factors was evaluated by IFE dan EFE matrix, mapped to the IE matrix to view the company's position. Strategy formulation with SWOT and QSP matrix. The result of feasibility analysis showed that seaweed cultivation efforts with longline method financially profitable and feasible. This was indicated by a positive NPV value of 30.81 million rupiah; B/C ratio (2.69), IRR (47.58%); PBP 1.61 years; BEP 13.23 million rupiah or sales of 1,474 kg of dried seaweed. With a total score value of the internal-external matrix of 2.52 and 2.83. The combination of these two values indicates that the position of the business lies in V cells or growth strategies. The most appropriate strategies are the empowerment of members and business groups to increase their business, and increased cultivation of technical skills for the improvement of product quality. These three strategies can be implemented simultaneously as mutually supporting one another.